Pain after Laparoscopic Cholecystectomy: Effect of IntraperitonealInfiltration of Injection Bupivacaine - Abdul Khaliq Mahar, Mujeebrehman Malik, Umme Habiba, Naveed Ali Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the effectiveness of intraperitoneal bupivacaine in patients undergoing laparoscopic cholecystectomy. Study Design: Prospective randomized study Place and Duration: Study was conducted at the department of SurgeryDow University Hospital (Ojha), Karachi for duration of six months from May 2021 to October 2021. Methods: There were 70 patients of both genders were presented in this study. Adult patients above 16 years of age, ASA class 1 & 2, undergoing elective cholecystectomy were included in this study. Informed written consent was taken from all the patients for detailed demographics age, sex and body mass index. Patients were categorized into 2 groups. Group A had 36 patients and received 40 ml of intraperitoneal infiltration 0.25% Bupivacaine at Gall Bladder bed and Right Subphrenic space. Group B control group with 34 patients received no intraperitoneal Bupivacaine. Both groups received 20 ml of 0.25% Bupivacaine at ports site incisions. All patients were educated about the standard Visual Analogue Score (VAS) pain score of 0 – 10, during pre anaesthetic evaluation visit. SPSS 23.0 version was used to analyze data. Results: There were 28 (77.8%) females in group A and in group B females were 31 (91.2%). 43.55±13.93 years were the mean age in group A and in group B mean age was 39.94±11.54 years. Mean body mass index of group A was 26.14±13.41 kg/m2 and in group II mean BMI was 25.06±11.53 kg/m2. In group B close technique was used in 26 (72.2%) while in group B 24(70.6%) cases received closed technique. Post-operatively low pain score was observed in study group as compared to group B. Frequency of rescue analgesic was higher in group B as compared to group A. Conclusion: We concluded in this study that the use of intraperitoneal bupivacaine for laparoscopic cholecystectomy was significantly effective in terms of low pain and is an effective method for improving the quality of life within the early recovery period.